Gaia: Complex systems prediction for time to adapt to climate shocks - Allen G. Hunt; Muhammad Sahimi; Boris Faybishenko; Markus Egli; Zbigniew J. Kabala; Behzad Ghanbarian; Fang Yu (Vadose Zone Journal)
Abstract Earth's climate has undergone significant fluctuations in the geologic past, while the sun's radiation continues to increase, yet has always returned to conditions highly favorable to life. Thus, the biosphere overall appears able to cancel effects of external trends as well as provide negative feedback to internal fluctuations. We focus on the glacial episodes that followed the major waves of invasion of land plants. Twice in Earth's history (Paleozoic), the impacts of land plant innovations on the atmosphere through increased CO2 drawdown have produced ice ages. In each case, the time between initial innovation and the emergence from the glacial episode was approximately 60 Myr. We postulate that the time for adaptation is a consequence of the time required for the spread of an entire clade through the soil to continental scale and that this time scale may be predicted using a scaling relationship verified for vegetation growth. We predicted these rates theoretically on the basis of the universal optimal two‐dimensional paths tortuosity from percolation. Comparison with 7000 actual data pairs for plant and fungal growth rates verified the accuracy of the scaling function over 13 orders of magnitude of time, from 1 min to 100 kyr. Extrapolation of the same relationship over less than three additional orders of magnitude of time yields a continental‐scale transport time of 80 Myr, similar to the time scale for recovery from Paleozoic ice ages. We interpret this prediction in terms of Margulis’ understanding of emergent behavior of coupled (soil and plant) ecosystems responding to climate shocks induced by plant innovations that produce renewed steady‐state between wood production and decay at a new equilibrium temperature.